Structural Analysis of Consumer Protection Failures in Indonesia - Fenny Bintarawati; Sigit Irianto; Sri Retno Widyorini; Nur Aini Fitriya Ardiani Aniqoh (Universitas Islam Negeri Walisongo Semarang, 2026)
This article critically examines the structural limitations of Indonesia’s consumer protection framework in light of Presidential Regulation No. 49 of 2024 on the National Consumer Protection Strategy. Although the regulation reflects renewed governmental attention to consumer welfare, this study questions whether it produces substantive legal reform or merely reinforces existing institutional patterns. Using a socio-legal approach that combines doctrinal analysis with empirical institutional data, the study identifies three persistent deficiencies: fragmented enforcement authority, inadequate redress mechanisms, particularly in digital transactions, and the predominance of non-binding regulatory design. The article introduces the concept of regulatory formalism to explain the gap between normative commitments and practical outcomes. Comparative insights demonstrate that effective consumer protection requires enforceable rights, institutional coherence, and accessible dispute resolution mechanisms. The findings suggest that National Consumer Protection Strategy does not resolve the structural weaknesses of Indonesia’s consumer protection regime. Meaningful reform therefore requires comprehensive statutory revision, institutional consolidation, and the establishment of binding digital dispute resolution systems. Artikel ini secara kritis mengkaji keterbatasan struktural kerangka perlindungan konsumen Indonesia berdasarkan Peraturan Presiden Nomor 49 Tahun 2024 tentang Strategi Nasional Perlindungan Konsumen (STRANAS-PK). Meskipun peraturan tersebut mencerminkan perhatian pemerintah yang diperbarui terhadap kesejahteraan konsumen, studi ini mempertanyakan apakah peraturan tersebut menghasilkan reformasi hukum substantif atau hanya memperkuat pola kelembagaan yang ada. Dengan menggunakan pendekatan sosio-hukum yang menggabungkan analisis doktrin dengan data kelembagaan empiris, studi ini mengidentifikasi tiga kekurangan yang terus berlanjut: kewenangan penegakan hukum yang terfragmentasi, mekanisme penyelesaian sengketa yang tidak memadai, khususnya dalam transaksi digital, dan dominasi desain peraturan yang tidak mengikat. Artikel ini memperkenalkan konsep formalisme regulasi untuk menjelaskan kesenjangan antara komitmen normatif dan hasil praktis. Wawasan komparatif menunjukkan bahwa perlindungan konsumen yang efektif membutuhkan hak yang dapat ditegakkan, koherensi kelembagaan, dan mekanisme penyelesaian sengketa yang mudah diakses. Temuan menunjukkan bahwa STRANAS-PK tidak menyelesaikan kelemahan struktural rezim perlindungan konsumen Indonesia. Oleh karena itu, reformasi yang bermakna membutuhkan revisi undang-undang yang komprehensif, konsolidasi kelembagaan, dan pembentukan sistem penyelesaian sengketa digital yang mengikat. Keywords: regulatory formalism; consumer protection; digital economy; institutional fragmentation; dispute resolution.